1999
DOI: 10.1042/0264-6021:3370193
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of vesicular monoamine transporter 2 in the pre-B cell line Ea3.123

Abstract: Uptake and storage of monoamines in secretory granules is accomplished by vesicular monoamine transporters, and it is likely that vesicular monoamine transporter 2 (VMAT2) is important for histamine transport in vivo. In the present study we have used the pre-B-cell line Ea3.123 to investigate the mechanisms involved in the transcriptional activation of the VMAT2 gene. In Ea3.123 cells, VMAT2 mRNA abundance was increased following mobilization of intracellular calcium, and this increased mRNA expression was pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…In contrast, absence of VMAT1 and VMAT2 from other cells of the hematopoietic and lymphoid lineage (e.g., eosinophil and neutrophil granulocytes, erythropoietic cells, lymphocytes and plasma cells) shows that vesicular monoamine storage mechanisms are restricted to megakaryocytes and basophil granulocytes. Though it has been suggested that VMATs can be transcriptionally activated in a preB-cell line and may be present in peripheral blood lymphocytes (Watson et al 1999; Amenta et al 2001), we could not confirm these observations in situ. Although there is strong evidence in the literature that lymphocytes synthesize catecholamines (Bergquist et al 1994; Josefsson et al 1996; Musso et al 1996), our results suggest that storage of monoamines in lymphocytes is not dependent on VMATs.…”
Section: Discussioncontrasting
confidence: 70%
“…In contrast, absence of VMAT1 and VMAT2 from other cells of the hematopoietic and lymphoid lineage (e.g., eosinophil and neutrophil granulocytes, erythropoietic cells, lymphocytes and plasma cells) shows that vesicular monoamine storage mechanisms are restricted to megakaryocytes and basophil granulocytes. Though it has been suggested that VMATs can be transcriptionally activated in a preB-cell line and may be present in peripheral blood lymphocytes (Watson et al 1999; Amenta et al 2001), we could not confirm these observations in situ. Although there is strong evidence in the literature that lymphocytes synthesize catecholamines (Bergquist et al 1994; Josefsson et al 1996; Musso et al 1996), our results suggest that storage of monoamines in lymphocytes is not dependent on VMATs.…”
Section: Discussioncontrasting
confidence: 70%
“…As in the basophil, the dendritic cell function of VMAT2 remains unclear, as do the domains of the VMAT2 gene that determine its expression in the hematopoietic cell lineage. It is of interest that pre-B cells express the VMAT2 gene, which is up-regulated along with the histidine decarboxylase gene by increased intracellular calcium (62).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Data about the mouse gene can now be assembled with data from the human cDNAs and genes from Uhl and colleagues, Xu and colleagues (57), Hasama, Uhl et al (unpublished results); from the rat gene from Watson and co‐workers (8); and from genomic databases to provide the human VMAT2 gene structures noted in Fig. 1.…”
Section: Vmat2 Genes: Human and Murine Genes Focal 5’ Sequence Consementioning
confidence: 99%
“…This 5′ flanking region is also rich in transcription factor recognition motifs. Approximately 2 kb portions of this region can drive reporter gene expression in rat lymphoid precursor cells that normally express VAMT2 (8). This promoter sequence fragment is also able to support expression of a sensitive reporter gene in SHSY‐5Y cells that normally express little VMAT2 (7).…”
Section: Vmat2 Genes: Human and Murine Genes Focal 5’ Sequence Consementioning
confidence: 99%